Perceptions of boundary ambiguity and parentification effects on family satisfaction, family support, and perceived stress in young adults of divorced families - Andsager, Kaylee (Kansas State University, 2015)
Using a sample of 109 students at a Midwestern university with divorced or separated parents I explored a) how sibling order and young adults’ age at parental divorce or separation impacted their experience of boundary ambiguity, parentification, stress, and family satisfaction and support, b) whether parentification mediated the effects of boundary ambiguity on stress, family support and family satisfaction, and c) whether sibling order moderated the relationship between these variables. I found that the child’s age at parental divorce/separation was positively correlated with boundary ambiguity, and negatively correlated with parentification, stress, family satisfaction, and social support. First or only children reported higher rates of parentification, specifically taking on a spousal role with their parents than younger siblings. Further, in divorced/separated families boundary ambiguity was positively related to young adults’ stress and negatively related to their levels of family satisfaction and family support both directly and indirectly through parentification. However, sibling order was not found to moderate the relationships between boundary ambiguity, parentification, family support, family satisfaction, and stress. Implications for theory and intervention are discussed.
Keywords: Boundary ambiguity; Parentification; Sibling order; Stress; Divorce; Family; Psychology (0621)